1997
DOI: 10.1164/ajrccm.156.2.9610116
|View full text |Cite
|
Sign up to set email alerts
|

Redefining End of Test (EOT) Criteria for Pulmonary Function Testing in Children

Abstract: In order for an individual FVC maneuver to be considered acceptable according to the 1994 American Thoracic Society (ATS) standards it must meet end of test (EOT) criteria of a minimum expiration time of 6 s with minimal volume change (0.03 L) over 1 s. We have found that while these criteria are often not met in children, most of the tests do meet the ATS criteria for reproducibility with repeated efforts. We, therefore, sought to develop new EOT criteria that would be more appropriate for children and in kee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 7 publications
0
19
0
Order By: Relevance
“…Because the ATS criteria in adolescents has been reported to be difficult [23][24][25][26][27][28][29][30][31], and excluding those not achieving ATS recommendations might exclude smokers, all students were included in the analysis. However, analyses were repeated excluding students not meeting the different Jaeger Masterscope ATS error codes with no significant differences in associations.…”
Section: Exercise and Sportsmentioning
confidence: 99%
“…Because the ATS criteria in adolescents has been reported to be difficult [23][24][25][26][27][28][29][30][31], and excluding those not achieving ATS recommendations might exclude smokers, all students were included in the analysis. However, analyses were repeated excluding students not meeting the different Jaeger Masterscope ATS error codes with no significant differences in associations.…”
Section: Exercise and Sportsmentioning
confidence: 99%
“…DESMOND et al [11] found comparable results. In their study, an FET of ¢6 s was reached by 28% and 7% of children over and under the age of 7 yrs, respectively.…”
Section: End-of-test Criteriamentioning
confidence: 76%
“…Curve-fitting techniques [20] may prove useful in developing new EOT criteria specific for young children.…”
Section: End Of Test Criteriamentioning
confidence: 99%